REKRUTMEN CALON ANGGOTA LEGISLATIF PARTAI KEADILAN SEJAHTERA KOTA PEKANBARU PADA PEMILIHAN LEGISLATIF TAHUN 2019 - Rizki "; Hasanuddin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This Skripsi discusses the system and mechanism of recruitment of candidates for legislative members conducted by PKS. The purpose of this study was to determine the recruitment carried out by PKS in recruiting candidates for legislative members. This research uses a qualitative method with a descriptive analysis case study. Data collection techniques used through interviews as primary data and literature study as secondary data.          The theoretical concept used by researchers is Political Recruitment which has an indicator of the tendency of political parties to recruit, namely, Partisans, Compartmentalization, Immediate Survival, and Civil Service Reform. This research uses qualitative research methods, with descriptive data review. In collecting data, researchers used interview and documentation techniques.          The results of this study indicate that, based on findings in the field, the recruitment of Candidates for PKS Legislative Members in Pekanbaru in the 2019 legislative elections was more dominant using the partisan type and Civil Service Reform in carrying out the process of recruiting prospective Legislative Members. This strengthens the process that is already running internally within PKS. and the Comparrmemalizarion type only supports the determination of prospective candidates and is considered by the party. But there are also factors that influence the recruitment of PKS legislative candidates, namely as supporting factors in recruitment are background, political experience, and financial. While the inhibiting factors are occupation, domicile of prospective candidates, and representation of women. It can be concluded that the recruitment of PKS Legislative Candidates can be said to have been good. So as to be able to produce qualified cadres and sympathizers to be candidates for legislative members. Keywords: Political Parties, Political Recruitment, Legislative Elections